ChemInform Abstract: Fast Synthesis of Complex Enantiopure Heterocyclic Scaffolds by a Tandem Sequence of Simple Transformations on α‐Hydroxyaldehydes. Issue 49 (3rd December 2013) - Cannillo, Alexandre; Norsikian, Stephanie; Retailleau, Pascal; Dau, Marie‐Elise Tran Huu; Iorga, Bogdan I.; Beau, Jean‐Marie
Abstract A novel sequence of tandem transformations, combining a first Petasis borono‐Mannich/intramolecular Diels—Alder transformation and subsequently a cross‐metathesis/conjugate addition reaction is reported.